The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/app7111151
|View full text |Cite
|
Sign up to set email alerts
|

Quality Changes of N-3 PUFAs Enriched and Conventional Eggs under Different Home Storage Conditions with Wireless Sensor Network

Abstract: Omega-3 polyunsaturated fatty acids (n-3 PUFAs) enriched eggs are popular for their enrichment of PUFAs, but their freshness and quality are prone to decline with time, particularly if storage conditions are not well maintained. Home storage is the last but a neglected important tach in eggs supply chain, but few studies are available on the egg storage in the home stage. This study aimed to evaluate the internal quality change of both n-3 PUFAs enriched and conventional eggs by simulating eggs stored at consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…This can presumably explain non-significant effects of DHA enrichment on lipid oxidative stability of yolk in this study. In addition, albumen height, HU, and YI values showed a significant reduction, whereas TBARS value showed an increase with the extension of storage time up to 28 D ( P < 0.05), in agreement with previous studies ( Mohiti-Asli et al., 2008 ; Li et al., 2017 ). No significant differences were observed in the internal qualities and oxidative stability of the eggs influenced by the interactions between storage days and dietary treatment ( P > 0.05).…”
Section: Resultssupporting
confidence: 92%
“…This can presumably explain non-significant effects of DHA enrichment on lipid oxidative stability of yolk in this study. In addition, albumen height, HU, and YI values showed a significant reduction, whereas TBARS value showed an increase with the extension of storage time up to 28 D ( P < 0.05), in agreement with previous studies ( Mohiti-Asli et al., 2008 ; Li et al., 2017 ). No significant differences were observed in the internal qualities and oxidative stability of the eggs influenced by the interactions between storage days and dietary treatment ( P > 0.05).…”
Section: Resultssupporting
confidence: 92%
“…Studies have shown that n-3 PUFAs have several health benefits, such as reducing the incidence of cardiovascular diseases, decreasing blood pressure and promoting the development of visual and cognitive abilities in infants and young children (Juturu, 2008;Lemahieu et al, 2015). n-3 PUFA enriched eggs are as highly perishable as conventional eggs, and their freshness and quality begin to decline immediately after production at the poultry farm (Li, Zhang, Jia, & Liu, 2017). Moreover, n-3 PUFAs increase the degree of unsaturation in egg yolk but may enhance the sensitivity to lipid oxidation (Galobart, Barroeta, Baucells, & Guardiola, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The lipids in eggs can be oxidized during storage, especially at high temperatures (Mohiti-Asli, Shariatmadari, Lotfollahian, & Mazuji, 2008). Therefore, the European Union recommends that the eggs were kept under refrigerator at home ((EC) No 589/2008and (EC) No 1234/2007, and the United States Department of Agriculture requires eggs to be stored at 7.2ºC or lower and at a relative humidity of 40 to 70% for during extended storage (Li et al, 2017). Most available data on egg quality are focused on normal eggs, whereas data on the effects of storage conditions on the quality of n-3 PUFA enriched eggs are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…However, only limited sensor observations are collected, because only sparse sensors are deployed in sensor networks given the high costs of sensors and limited budget. Due to limited sensing With the development of sensor technologies, wireless sensor networks have emerged as a key tool to collect sensing data and enable the sensing data to measure the fields [17][18][19]. Many researchers have employed statistical methods for the estimation of temperature fields using sensing observations, which aim to capture stochastic dynamics and uncertainties of temperature fields.…”
Section: Introductionmentioning
confidence: 99%